Financial distress and earnings management before and during the Covid-19 pandemic - Novy Fajriati; Ersa Tri Wahyuni; Dini Rosdini (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This study aims to investigate the influence of financial distress on accrual earnings management and real earnings management before and during the COVID-19 pandemic. Using a purposive sampling method, the study analyzed the sectors most impacted by the pandemic lockdown, including energy, transportation, and logistics companies, between 2018 and 2021. The total sample of 236 firm-year observation data points was analyzed in this study using regression analysis. The study finds that financially distressed firms tend to engage less in real earnings management before and during the COVID-19 pandemic. However, the study did not find a similar significant difference for accrual earnings management. This research contributes to the discussion of financial distress and earnings management by looking more closely to the company most affected by the pandemic. Real earnings management is more costly than accrual earnings management, and companies with financial distress may not have enough resources, especially during the pandemic, to maneuver their real business operations.